The effects of teacher-pertinent factors and teacher motivation on Hong Kong English teachers’ motivational strategies - Shu Yang Lin; Tim S. O. Lee (Cogent Education)
Teachers’ motivational support is crucial for the enhancement and maintenance of English learners’ motivation, yet there has been little enquiry into the factors which drive English teachers to use motivational strategies. Although considerable research has shown links between student and teacher motivation, the assumption that motivated teachers make more frequent and thoughtful motivational efforts has been largely untested. This study, analysing journal and interview data collected from 13 Hong Kong English teachers over a semester, aims to uncover how English teachers’ motivational behaviour is shaped by teacher-pertinent factors, and how these factors reflect different facets of teacher motivation. Preparation workload, teaching style, peer sharing, and various self-benefits were found to be influential factors originating from the teachers. The notions of intrinsic teacher motivation, ideal teacher selves, work satisfaction, and demotivation were manifest in the teachers’ responses. The findings have implications for school management, teacher trainers, English teachers, and researchers.